Formation of pre-metastatic bone niche in prostate cancer and regulation of traditional chinese medicine - Chen, Chiwei; Huang, Renlun; Zhou, Jianfu; Guo, Lang; Xiang, Songtao (Frontiers in Pharmacology, 2022)
Prostate cancer with bone metastasis has a high cancer-specific mortality. Thus, it is essential to delineate the mechanism of bone metastasis. Pre-metastatic niche (PMN) is a concept in tumor metastasis, which is characterized by tumor-secreted factors, reprogramming of stromal cells, and immunosuppression by myeloid-derived suppressor cells(MDSC) which is induced by bone marrow-derived cells (BMDC) in the target organ. However, PMN does not explain the predilection of prostate cancer towards bone metastasis. In this review, we discuss the initiation of bone metastasis of prostate cancer from a perspective of PMN and tumor microenvironment in a step-wise manner. Further, we present a new concept called pre-metastatic bone niche, featuring inherent BMDC, to interpret bone metastasis. Moreover, we illustrate the regulation of Traditional Chinese medicine on PMN.